Tourism Sector Performance Analysis in North Sulawesi: Challenges and Opportunities for Increased Visits - Lakat, Junior; Kumenaung, Anderson Guntur; Lengkong, Victor Paskah Kalawat; Gamaliel, Hendrik; Mumek, Leonard Stiefen (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This research article analyzes the performance of the tourism sector in North Sulawesi, focusing on the challenges and opportunities that influence the increase in tourist visits. The study highlights the significance of tourism as a strategic sector for economic growth, community welfare, and cultural preservation. Utilizing a qualitative methodology, the research examines various performance indicators, including productivity, service quality, responsiveness, responsibility, and accountability. The findings reveal that while North Sulawesi has substantial tourism potential, it faces significant challenges such as inadequate infrastructure, limited market diversification, and low innovation in tourism products. The dominance of Chinese tourists underscores the need for a diversification strategy to attract visitors from other regions. The study concludes with recommendations for enhancing tourism management practices, improving service quality, and fostering collaboration among stakeholders to ensure sustainable growth in the tourism sector.